Sensitivity of fecal immunochemical test for colorectal cancer detection differs according to stage and location - Niedermaier, Tobias; Tikk, Kaja; Gies, Anton; Bieck, Stefanie; Brenner, Hermann (Clinical gastroenterology and hepatology, 2020)
Background & Aims - Fecal immunochemical tests (FITs) are widely used for colorectal cancer (CRC) screening. FITs detect most CRCs. Although detection of CRC at early stages is most relevant for reducing CRC mortality, there is limited evidence for the stage-specific sensitivity of the FIT in CRC detection. We estimated stage- and location-specific sensitivities of a quantitative FIT in a large cohort of patients with CRC. - Methods - Fecal samples were collected before treatment from 435 patients with newly diagnosed CRC. Sensitivities of a quantitative FIT (FOB Gold, Sentinel Diagnostics; Milano, Italy) for tumors of different T stages and overall TNM stages (according to Union for International Cancer Control) were calculated at the cutoff recommended by the manufacturer (17 μg/g feces) and at alternative cutoffs, ranging from 10 to 40 μg/g feces, overall and stratified by tumor location. - Results - At the cutoff recommended by the manufacturer, the FIT detected T1 tumors with 52% sensitivity (95% CI, 37%-67%), T2 tumors with 79% sensitivity (95% CI, 68%-88%), T3 tumors with 93% sensitivity (95% CI, 89%-95%), and T4 tumors with 84% sensitivity (95% CI, 72%-92%) (Ptrend < .0001). The FIT detected stage I cancers with 68% sensitivity (95% CI, 57%-78%), stage II cancers with 92% sensitivity (95% CI, 87%-96%), stage III cancers with 82% sensitivity (95% CI, 73%-89%), and stage IV cancers with 89% sensitivity (95% CI, 80%-95%) (Ptrend 0.01). The FIT detected T1 colorectal tumors with sensitivity values that were 22%-52% lower than for tumors of other T stages and stage I CRC with sensitivity values that were 11%-33% lower than for later-stage CRCs, at any of the evaluated cutoff values. The FIT detected T1 and stage I CRCs in the distal colon with sensitivity values of 32% and 52%, respectively. - Conclusions - Although the FIT identifies patients with CRC with overall high sensitivity, it can miss approximately one-third of stage I CRCs. Studies are needed to increase noninvasive detection of early-stage CRC.
Gesehen am 21.12.2020